2015
DOI: 10.1080/14693062.2015.1033675
|View full text |Cite
|
Sign up to set email alerts
|

Helping eco-labels to fulfil their promises

Abstract: "Gilles Grolleau and Naoufel Mzoughi thank the research programme ‘GESSOL’, sponsored by the French Ministry of Ecology, Sustainable Development and Energy"The economic literature has devoted relatively strong attention to eco-labelling schemes. Nevertheless, while succeeding in some markets, they often fall short of their promises. We analyse the gap between the academic design of eco-labelling schemes and their real implementation. We contend that providing information is not enough. We then use recent advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 54 publications
2
24
1
Order By: Relevance
“…Consumer awareness through more information and education about eco-labels has been cited as a way to improve adoption (Harbaugh, Maxwell, and Roussillon 2011; Madurah, Reiners, and Wood 2016). Behavioural approaches should be used, such as making sustainability issues feel important to consumers (Grolleau et al 2016). Horne (2009) criticises label simplicity as a solution and found it does not ease inter-product comparisons and undermines label efficacy.…”
Section: Literature Summarymentioning
confidence: 99%
“…Consumer awareness through more information and education about eco-labels has been cited as a way to improve adoption (Harbaugh, Maxwell, and Roussillon 2011; Madurah, Reiners, and Wood 2016). Behavioural approaches should be used, such as making sustainability issues feel important to consumers (Grolleau et al 2016). Horne (2009) criticises label simplicity as a solution and found it does not ease inter-product comparisons and undermines label efficacy.…”
Section: Literature Summarymentioning
confidence: 99%
“…Ecolabels are intended to allow consumers to make informed choices that reduce environmental impact and influence how products are made (Rex and Baumann, ). A great deal of effort has been put into ecolabels; however, research has shown that companies fulfilling all ecolabel criteria do not always lead the consumer to sustainability purchasing decisions (Thøgersen, ; Leire and Thidell, ; Rex and Baumann, ; Grolleau et al , ). The effectiveness of ISO 14001 in reducing environmental impacts also remains mixed (Arimura et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Schubert () argues that although it is generally conceived that providing consumers with additional information necessarily improves their choices, things are different in the real world. Findings in behavioral sciences suggest that well‐crafted eco‐labels do much more, such as reducing individuals' cognitive dissonance, overcoming loss aversion issues, and conveying social norms (Beretti, Grolleau, & Mzoughi, ; Grolleau et al, ; Schubert, ). In the same vein, we argue that eco‐labels are sometimes perceived as harming the product rather than improving it.…”
Section: Conceptual Framework and Main Hypothesismentioning
confidence: 99%
“…Promoting the green benefits of products can be considered as a simple and direct way to harness the power of green consumption in order to contribute to sustainable development goals (Grolleau, Ibanez, Mzoughi, & Teisl, ). Nevertheless, how do consumers judge products usual functions or instrumentality when they are informed that the considered products also deliver green benefits?…”
Section: Introductionmentioning
confidence: 99%